Pengaruh Pembelajaran Realistic Mathematic Education (RME) terhadap Prestasi Belajar Siswa Kelas V SDN Sekemandung 1 Kab. Bandung dalam Materi Volume Bangun Ruang - Fajrin, Siti Nuraini; Samadi, Mochammad Ramdan; Mayasari, Annisa; Hani, Umi (Prodi PGMI STAI Sabili Bandung, 2024)
The effectiveness of the Realistic Mathematics Education (RME) method compared to conventional methods was evaluated at SDN Sekemandung 1. The importance of this topic lies in the urgent need for more effective mathematics teaching methods, given the challenges and difficulties often faced by students in this subject at the elementary school level. The research was conducted from February to March during the 2023/2024 academic year using a Quasi-Experimental design, involving two groups: Class VA as the experimental group using RME and Class VB as the control group using conventional methods, each consisting of 29 students. Mathematics learning outcomes were assessed through tests measuring students' understanding before and after the method's implementation. The study found that the average score for the experimental class was 85.34, while the control class scored 79.48, with a significant difference indicating the superiority of RME. This analysis suggests that the RME method is significantly more effective in improving mathematics learning outcomes at the elementary level compared to conventional methods, and it is recommended for broader application to enhance the quality of mathematics education.